2023
DOI: 10.1002/adma.202207798
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐Free Transfer of Freestanding Large‐Area Conjugated Polymer Films for Optoelectronic Applications

Abstract: Conventional processes for depositing thin films of conjugated polymers are restricted to those based on vapor, liquid, and solution‐phase precursors. Each of these methods bear some limitations. For example, low‐bandgap polymers with alternating donor–acceptor structures cannot be deposited from the vapor phase, and solution‐phase deposition is always subject to issues related to the incompatibility of the substrate with the solvent. Here, a technique to enable deposition of large‐area, ultra‐thin films (≈20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…To avoid destruction of the Y7-BO smallmolecule layer by solvents used in typical sequential spin coating (SC) processes, we transferred a PM6 polymer layer formed separately on water via the spontaneous spreading (SS) phenomenon caused by the Marangoni effect, which has been utilized for applications involving the R2R process. [66][67][68] Coating the top layer via the SS process, which is otherwise almost impossible, enabled the realization of an inverted structure. The face-on orientation of the SS-processed polymer lms was reinforced by optimizing the amount of a solvent additive, i.e., 1-chloronaphtalene (CN).…”
Section: Introductionmentioning
confidence: 99%
“…To avoid destruction of the Y7-BO smallmolecule layer by solvents used in typical sequential spin coating (SC) processes, we transferred a PM6 polymer layer formed separately on water via the spontaneous spreading (SS) phenomenon caused by the Marangoni effect, which has been utilized for applications involving the R2R process. [66][67][68] Coating the top layer via the SS process, which is otherwise almost impossible, enabled the realization of an inverted structure. The face-on orientation of the SS-processed polymer lms was reinforced by optimizing the amount of a solvent additive, i.e., 1-chloronaphtalene (CN).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the realization of conformal transfer of several cm 2 2PP structures was obtained, as shown in Figure S9 (Supporting Information). Furthermore, both large‐scale nanofilm preparation techniques [ 48 ] and feasible large‐scale nanofilm transfer from the water surface [ 49 ] enable the application of the proposed 2PP printing handling method to on‐demand surface areas.…”
Section: Transfer Printing Of 2pp 3d‐microstructures Via Nanomembranesmentioning
confidence: 99%
“…Furthermore, UFTM can also be applied to multilayer system consisting of single material as well as heterojuction structure, i.e., multilayers with different materials. [25,26] In this work, we have utilized UFTM as a simple, facile cost/material utilization-effective technique to fabricate large area and oriented thin films regioregular poly(3-hexylthiophene) (RR-P3HT) as a representative solution processable CP. Oriented multiple layers of the thin films of this polymer were successfully fabricated and demonstrated that there was no detrimental effect on the underlying layer as confirmed by optical, microstructural, and electrical characterizations.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, UFTM can also be applied to multilayer system consisting of single material as well as heterojuction structure, i.e., multilayers with different materials. [ 25,26 ]…”
Section: Introductionmentioning
confidence: 99%